PERENCANAAN ANGGARAN BIAYA DAN WAKTU PELAKSANAAN PEKERJAAN STRUKTUR LAUNDRY ZEST HOTEL AMBON BERDASARKAN AHSP PERMEN PU 28/PRT/M/2016 - Pattikawa, Elena Julian; Saleh, La Mohamat; Gaspersz, Willem (Jurusan Teknik Sipil, 2024)
To restore the level of project progress according to the planned cost and time, appropriate planning is needed to obtain optimal project costs and duration. These parameters are planned to achieve project targets within cost and time constraints. The Zest Hotel Ambon Laundry construction project reviewed by the author is a privately funded project with a tentative implementation time so that there are no binding elements in terms of both cost and project implementation time. For this reason, the author will plan the budget and implementation time based on AHSP Minister of Public Works Regulation 28/PRT/M/2016. The aim of this research is to obtain more accurate estimates so that the project can be managed well, can achieve the desired goals, and stay within the budget and time limits that have been set. From the results of budget planning calculations for the implementation of the Zest Hotel Ambon Laundry structure based on AHSP Minister of Public Works Regulation 28/PRT/M/2016, the cost was IDR 1,193,329,721.76. Meanwhile, planning the project implementation time based on the standard AHSP coefficient of PU Ministerial Decree 28/PRT/M/2016 using the CPM method and the application of Microsoft project software, the total project duration was 172 calendar days